Reduced cerebral blood flow but elevated cerebral glucose metabolic rate in erythropoietin overexpressing transgenic mice with excessive erythrocytosis - Frietsch, Thomas; Maurer, Martin H.; Vogel, Johannes; Gassmann, Max; Kuschinsky, Wolfgang; Waschke, Klaus F. (Journal of cerebral blood flow & metabolism, 2007)
To examine the impact of excessive erythrocytosis on local cerebral blood flow (CBF) and cerebral glucose metabolic rate (CMRglc), we made use of our constitutively erythropoietin (Epo)-overexpressing transgenic mouse line (tg-6) that reach a mean hematocrit of 0.87. Compared with wild-type (wt) control siblings, CBF decreased by 44% in tg-6 mice, while upon hemodilution (tg-6-HD) to a physiologic hematocrit (e.g., 0.44) tg-6-HD mice returned the CBF to wt levels. Cerebral blood flow was determined in another transgenic mouse line that overexpresses human Epo in the brain only (tg-21): CBF increased by 17% compared with wt controls. However, oxygen delivery was similar in all four mouse groups tested (wt, tg-6, tg-6-HD and tg-21). Mean CMRglc was higher in tg-6 (+72%), tg-6-HD mice (+43%) and tg-21 (+22%) than in wt mice. Local CMRglc was higher in all 40 brain regions in tg-6 but only in 15 and 8 regions in tg-6-HD and tg-21 mice. These results show that prolonged increases in hematocrit did not alter cerebral oxygen delivery at a decreased CBF and increased CMRglc. Hemodilution suggests that high blood viscosity is a cause of the decrease in CBF and partly of the increase in CMRglc. Cerebral glucose metabolic rate may also be increased by a direct effect of Epo in the brain (tg-21 mice).
Gesehen am 30.04.2021